The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/aem.69.8.4352-4358.2003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the RpoS Status of Clinical Isolates of Salmonella enterica

Abstract: The stationary-phase-inducible sigma factor, S (RpoS), is the master regulator of the general stress response in Salmonella and is required for virulence in mice. rpoS mutants can frequently be isolated from highly passaged laboratory strains of Salmonella. We examined the rpoS status of 116 human clinical isolates of Salmonella, including 41 Salmonella enterica serotype Typhi strains isolated from blood, 38 S. enterica serotype Typhimurium strains isolated from blood, and 37 Salmonella serotype Typhimurium st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 51 publications
8
51
0
Order By: Relevance
“…However, it is not clear whether this mutation was present in the original isolate or is a result of laboratory passage. In one recent study, 36% of fresh human S. Typhi isolates were found to be rpoS mutants [53]. We confirmed that the rpoS allelic state is in fact responsible for these observations by constructing an rpoS deletion in ISP1820 [51].…”
Section: Effect Of Rpos On VI Synthesissupporting
confidence: 70%
“…However, it is not clear whether this mutation was present in the original isolate or is a result of laboratory passage. In one recent study, 36% of fresh human S. Typhi isolates were found to be rpoS mutants [53]. We confirmed that the rpoS allelic state is in fact responsible for these observations by constructing an rpoS deletion in ISP1820 [51].…”
Section: Effect Of Rpos On VI Synthesissupporting
confidence: 70%
“…The competition between the drive for protection against stress via a functioning s 38 , and improved scavenging via increased s 70 leads to varied mutations in rpoS (Notley-McRobb et al, 2002;Chen et al, 2004;King et al, 2004;Ferenci, 2005;Mandel and Silhavy, 2005;Maharjan et al, 2006). rpoS mutations have been identified in clinical isolates of S. enterica serovar Typhi (Robbe-Saule et al, 2003), though are rare, and are not demonstrated in serovar Typhimurium, thus it is unclear whether these mutants truly exist in clinical settings. This study emphasizes how easy it is to generate rpoS mutations in the laboratory and care must be taken in clinical studies to ensure that rpoS À mutants are not selected by accident from an rpoS þ ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…The other isolates, Sarc4 and Sarc16, were identified as being RpoS deficient. Mutations in rpoS have been detected in other Salmonella isolates and are thought to reflect either natural variation or laboratory-induced changes (34,47,60).…”
Section: Discussionmentioning
confidence: 99%